1999
DOI: 10.1002/(sici)1097-4636(1999)48:4<474::aid-jbm11>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of fatigue cracks in ultrahigh molecular weight polyethylene joint components by the addition of vitamin E

Abstract: Flaking-type wear, so-called delamination, is often observed in polyethylene joint components. This is thought to occur partly due to crack formation and propagation at grain boundaries. This study examined the effect of vitamin E on the crack formation and/or propagation in UHMWPE by using 2-dimensional sliding fatigue testing and micro indenter testing. An in vitro sliding fatigue test was performed under two simplified articulating movements, and the cracks produced were observed by scanning acoustic tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(40 citation statements)
references
References 14 publications
(17 reference statements)
3
35
0
Order By: Relevance
“…Also it has shown potential for the reduction of off-flavours related to polymer oxidation during processing [22]. Recently vitamin E has also been found to prevent fatigue cracks in UHMWPE for medical implants [23]. Vitamin E activity at >120 Ci n oxidising polypropylene was found to be very effective, but less so than some other industrial phenols [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Also it has shown potential for the reduction of off-flavours related to polymer oxidation during processing [22]. Recently vitamin E has also been found to prevent fatigue cracks in UHMWPE for medical implants [23]. Vitamin E activity at >120 Ci n oxidising polypropylene was found to be very effective, but less so than some other industrial phenols [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, the previous studies [51,52,58] showed that vitamin E alone with up to 0.4 wt% concentration have a marginal effect on the mechanical properties of UHMWPE. However, some studies [44,57,59] suggested that vitamin E-stabilised UHMWPE has a significantly higher tensile strength, yield strength, elongation at break and fatigue resistance, especially at concentrations exceeding 0.1 wt% [59]. More detailed information on the mechanical properties of vitamin E-stabilised UHMWPE is shown in Table 2.…”
Section: Effect Of Vitamin E On Tribological and Mechanical Propertiementioning
confidence: 99%
“…A study comparing the wear of vitamin E-blended (0.3 wt%), unirradiated UHMWPE versus conventional UHMWPE in a knee simulator showed lower wear volume and different debris for the former [75], suggesting vitamin E alone may improve the wear/delamination resistance [77].…”
Section: Effects Of Vitamin E On Microstructure Tribologic and Mechmentioning
confidence: 99%